Prevalence of Intradialytic Muscle Cramps and Quality of Life in Haemodialysis Patients - Somiya Naz; Mubashar Nazar; Waqas Khalid; Laraib Akhtar Malik; Abeera Tahir; Muhammad Mujtaba Ur Rehman (Journal of Bahria University Medical and Dental College)
Objective: The aim of this study was to find out prevalence of intradialytic muscle cramps and quality of life in hemodialysis patients.